ULTRASONIC EXAMINATION OF VENTILATION TUBES PATENCY IN PATIENTS WITH OTITIS MEDIA WITH EFFUSION AFTER TIMPANOSTOMY - N. V. Shcherbik; V. A. Konushkin; A. V. Starokha; M. M. Litvak (Бюллетень сибирской медицины, 2014)
The aim of this study was to improve the accuracy and sensitivity of methods for ventilation tube patency evaluation after timpanostomy. New method of one-dimensional ultrasound middle ear sonography was developed. We studied ventilation tubes patency in 40 patients with otitis media with effusion, after timpanostomy. All patients tympanometry and one-dimensional ultrasound sonography was obtained at 4, 7th and one month after surgery. After timpanostomy in children with the otitis media with effusion, at 4 days after the surgery one-dimensional ultrasound sonography detected normal function of ventilation tubes in 75% patients. At the same time, according to tympanometry ventilation tube patency was recorded in 80% patients. On 7th  day after surgery one-dimensional ultrasound sonography detected normal function of ventilation tubes in 85% patients. According to tympanometry the 90% patients demonstrated normal ventilation tube function. One month after surgery one-dimensional ultrasound sonography detected normal function of ventilation tubes in 92.5% patients. At the same time, according to tympa nometry ventilation tube patency was recorded in 95% people. Calculation of ultrasound sonography sensitivity and specificity showed that the sensitivity of this process is 97.4%, specificity – 100%. The statistical significance of differences in ventilation tube patency assessment is not determined. Thus, we have proved one-dimensional ultrasound sonography the sensitive method for ventilation tubes patency validation. The method is simple, requires a bit of time for application, so it can be widely recommended for outpatient network.